Gastroesophageal Reflux Disease in children – clinical picture, diagnostic methods, and treatment: A literature review (Research, Society and Development, 2024)
Gastroesophageal reflux disease (GERD) is a common condition in children, characterized by the abnormal reflux of gastric contents, with variable presentations depending on age, and with potential clinical complications. This study aims to review the literature on gastroesophageal reflux disease in children, its diagnostic methods and available treatments. In addition, it is intended to be the final work of the Medical Residency in Pediatric Surgery at the State University of Piauí (UESPI). The methodology included the search for articles in databases such as PubMed, Scielo, Medline and Cochrane Library, using keywords related to the topic. Studies in Portuguese and English were selected, including original articles, systematic reviews and clinical guidelines. Exclusion criteria were applied to discard case reports and studies focusing on adults. The results indicated that the main symptoms of GERD in children vary according to age, including regurgitation, irritability, abdominal pain and respiratory difficulties. The most used diagnostic methods are esophageal pH monitoring and endoscopy, while treatment includes dietary measures, proton pump inhibitors, and surgery in severe cases. The study concluded that although there have been advances in the understanding and management of GERD in children, challenges remain, such as accurate diagnosis in atypical cases and choosing the most appropriate treatment for each age group. Further research is recommended to address these gaps and improve the effectiveness of therapeutic interventions.